Effects of Supplier-Manufacturer Relationships on Supply-Chain Performance of Manufacturing Industries in Indonesia - Hidayat, Rachmad; Hudha, Khisbullah; Akhmad, Sabarudin (Makara Journal of Technology, 2015)
The present study describes the relationships between commitment, communication, satisfaction, trust, relationship quality with suppliers, and supply-chain performance. The population of the study was manufacturing companies in Indonesia. Respondents were the chief executive officers or corporate secretaries or the designated managers involved in strategic decision making. Samples were taken by using a proportional area random sampling technique. Structural Equation Modeling (SEM) was used for analysis. Results of both direct and indirect testing of hypothesis indicated two hypotheses of positive and significant effects and nine hypotheses of positive but insignificant effects. Those hypotheses of positive and significant effects were the direct effects of trust on supply-chain performance and the direct effects of relationship quality on supply chain performance.